Mechanical Properties of Titanium Films Deposited by Pulsed High-Power Ion Beams; 7 International conference on modification of materials with particle beams and plasma flows - Struts V. K.; Matvienko V. M.; Petrov A. V.; Ryabchikov A. I. Aleksandr Ilyich; Shlapakovski A. S. (Coating deposition, 2004)
Title from the title-page.